Should blind judokas and partially sighted judokas compete together? A reflection from the study of the temporal structure of combat - Gutiérrez-Santiago, J. A.; Prieto-Lage, I.; Paramés-González, A.; Argibay-González, J. C.; Reguera-López-de-la-Osa, X.; Gutiérrez-Santiago, A. (Journal of Human Kinetics, 2023)
The investigation of the temporal structure of Para judo combat according to sport classes or visual categories (B1, B2 and B3) has only been carried out in women. The objectives of the study were to analyze the differences in the temporal structure of combat between the male para-judokas sport classes, and to determine whether blind judokas and partially sighted judokas should compete together. All para-judokas who competed in the 2018 IBSA Judo World Championships (172 men) participated in the study. Using observational methodology, we analyzed all the combats (n = 232). To obtain the results, we used different analysis techniques: descriptive, one-way ANOVA, t-test for independent samples and effect size. The level of significance established for the study was ? = 0.05. The results indicate that during pauses, time dedicated to displacement was increased when there was a B1 judoka in the pairing, causing pauses to be significantly longer. Coaches should take this into account. In conclusion, there are differences between particular visual categories. B1 judokas have longer pauses, perform more ground fighting sequences and win fewer combats. The competition is not on equal terms. More research is needed in order to determine if new regulations have modified the combat temporality.